Modelos volumétricos e fator de forma na estimativa do volume de árvores em cerrado sensu stricto - Medeiros, Paulo César Alves de Oliveira (Universidade Federal do Tocantins, 2018)
The work aimed to make the horizontal structure characterization through the importance value index (IVI) and specific objectives to determine the volume of ten wood species with larger field in a Cerrado sensu stricto fragment in the municipality Gurupi-TO, through the use of volumetric and equation of the form factor. The data was from standing trees relative space and their volumes obtained by the Hohenadl equation (10 sections). 323 diameters were collected trees-samples in 5 diamétricas classes, with intervals of 2 cm. 10 volumetric models were selected, these being called: Ogaya, Stoate, Raj et al. (2006), Scolforo and Silva (1993), Meyer, Spurr (Logarithm) Kopezky-Gehrhardt, Hohenadl-Krenn, Brennac and Schumacher-Hall, for the adjustment of the data. For evaluating statistical criteria adopted: R ² aj, Syx, in addition to the graphical analysis of the distribution of waste. For the 10 species obtained an average productivity in terms of basal area of 7.05 m ² ha-1 and volumes estimated by equation and by form factor, 25.25 values m3 ha-1 and 26.87 m3 ha-1, respectively. The average form factor was 0.67 for the 10 species evaluated. It is concluded that form factor can be used for the volume estimates in areas where a dominance of species or groups of species with similar characteristics to this study, especially in areas of Cerrado sensu stricto as an alternative the volumetric and equations that model of Meyer presented the best performance for volume estimation in 10 species in an area of Cerrado sensu stricto.